Does Assertiveness Correlate with Second-Year Student Adjustment in the College? - Maria Nugraheni Mardi Rahayu (Universitas Ahmad Dahlan, 2023)
This research aims to identify if there is a relationship between assertiveness and adjustment in second-year students at tertiary institutions. There are 264 SWCU Psychology Faculty second-year students as the research participants (average age = 19.23 years, SD = 0.85 years, 71.97% female). This research uses two measurement instruments, namely the Assertiveness Formative Questionnaire and the Students' Adjustment to College Questionnaire. The correlation test results show that there is a significant positive relationship between assertiveness and academic adjustment (r = 0.381, sig. = 0.000), social (rs = 0.438, sig. = 0.000), personal-emotional (r = 0.207, sig. = 0.001) and institutional attachment (rs = 0.249, sig. = 0.000). It means that a higher level of assertiveness possessed by the students reflects higher levels of academic, social, and personal-emotional adjustments, and institutional attachment. These findings can be a reference for other institutions to provide specific programs to increase the students’ assertiveness to assist them in the adjustment process